Enhanced photocatalytic activity of copper-doped titanium oxide using zinc oxide heterojunction and iodide co-doping for water treatment application / Masoumeh Dorraj - Masoumeh , Dorraj (2018)
Doping titanium dioxide (TiO2) with 3d transition metal elements is a popular technique that facilitates its visible-light-induced photocatalytic performance. However, many experimental reports indicate that these dopants in TiO2 lattice are recombination centers, which resulted in limited enhancement of photocatalytic activity. Thus, designing a photocatalyst composed of semiconductor heterojunctions and nonmetal co-dopants are viable approaches to address this challenge. In this thesis, Cu doped TiO2 was coupled with ZnO (Cu-TiO2/ZnO) at different molar ratios by sol-gel method and subsequent precipitation. The apparent rate constants are 0.0011, 0.0166, and 0.0306 min−1 for TiO2, 3% Cu-TiO2, and 3% Cu-TiO2/30% ZnO, respectively. Thephotocatalytic activity of the 3% Cu-TiO2/30% ZnO nanocomposite is approximately 2-folds higher than that of 3% Cu-TiO2 nanoparticles and 28-folds higher than that of bare TiO2 during degradation of methyl orange (MO). The enhanced photocatalytic activity of the Cu-TiO2/ZnO nanocomposites was mainly attributed to the heterojunction formation, which allowed the efficient separation of photoinduced electron−hole pairs at the interface. Cu-I-co-doped TiO2 nanoparticle photocatalysts responsive to visible light were also prepared through hydrothermal treatment and calcined at different temperatures (350, 450 and 550 °C). The co-doped powders calcined at 350 °C showed the largest BET surface area and the decrease in photoluminescence intensity demonstrated that the electron-hole recombination was also decreased. The synthesis of co-doped TiO2, mono-doped TiO2 and pure TiO2 was performed at this optimized temperature. The presence of Cu2+ and I5+ in the XPS spectrum indicated that the Cu2+and I5+ substituted the titanium (Ti4+) in TiO2 lattice. The degradation rate constant (k) of Cu-I-co-doped TiO2 (0.030 min−1) is about 1.67 and 1.5 larger as compared to the kvalue of the Cu mono-doped TiO2 (0.018 min−1) and I mono-doped TiO2 (0.020 min−1)under visible light irradiation. The enhanced photocatalytic activity is due to the strong visible light absorption and effective separation of the photogenerated charges caused by the Cu and I co-dopants.